Architecture of Absurd - Fross, Klaudiusz; Ujma-Wąsowicz, Katarzyna; Wala, Ewa; Winnicka-Jasłowska, Dorota; Gumińska, Anna; Sitek, Michał; Sempruch, Agata (Universal Access in Human-Computer Interaction. Methods, Techniques, and Best Practices, 2016)
Ergonomy is not automatically attributed for an architectonic projects. Construction regulations and norms partially guarantee ergonomic solutions. But still, there is a free, great field for creative work (visions, ideas) for designer. Architects can, but do not have to, use ergonomic principles in projects. They can also freely omit them. We know, that high quality ergonomic buildings are functioning, in built environment, as well as unergonomic and ineffective ones, so-called “ill”. Why is it like that? Why architects are enabled to design unergonomic, “ill” objects? Why the investor agrees to inefficient building? Is such an object a success or a failure? Authors think that this subject is extremely current, because it makes us notice, a big amount of basic project errors in buildings. The article presents and discusses examples of pleasing from the outside but non-ergonomic, ineffective and non-functional buildings - the masterpieces of architecture. This type of design is called - “the architecture of absurd” (Fross 2015). It also indicates that using a methodology of qualitative research, evaluate the design at the stage of concept and programming. Design with the principles of ergonomics guarantees the future quality of the object [5].